Russian Pilots Arrive in Vancouver - Washington State University Vancouver Library; http://library.vancouver.wsu.edu/ (1937)
The Soviet Russian plane arrived in Vancouver after a record breaking transpolar flight from Russia in 1937. The first non-stop flight over the North Pole. 5x7 in.